Keteladanan Kepala Rumah Tangga Sebagai Penatua Jemaat Untuk Pertumbuhan Gereja Berdasarkan 1 Timotius 3:5 - Anfranklin Lumbanraja; Stimson Hutagalung; Rudolf Weindra Sagala (Sekolah Tinggi Filsafat Seminari Pineleng, 2021)
This essay aims to find a correlation between the life example of the head of the household who acts also as a leader of the congregation and the growth of the Church. The author uses the statement in 1 Timothy 3:5 as the basic text, as well as the main inspiration for this description. The methodology used by the author in this research is a literature study. The author develops the topic of discussion by reviewing books, scientific articles, and other literature that discussed the same topic. Based on the analysis of the text of 1 Tim 3:5 the author emphasizes the importance of a church leader who is proven to be responsible for household affairs, namely being able to manage his own house and meet the needs of family members. The reputation of the Church in the development of the congregation will depend on the example of the church leader in managing his own household and his congregation.